2018
DOI: 10.1002/hed.25486
|View full text |Cite
|
Sign up to set email alerts
|

Oral and pharyngeal cancer risk associated with occupational carcinogenic substances: Systematic review

Abstract: Background Oral and pharyngeal cancers (OPC) represent the seventh most common type of cancer and the seventh leading cause of deaths by cancer worldwide. Few studies have assessed the occupational exposure risks associated with OPC and in many cases the results are conflicting. The aim of this study was to determine, through a systematic review, the association of OPC and exposure to different occupational carcinogenic substances. Methods The addressed focused question was “Is there an association of occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 35 publications
(114 reference statements)
0
19
0
1
Order By: Relevance
“…Betel quid chewing, which is popular in India and other Asian countries, has also been shown to increase the risk of HNSCC (mainly oral cancer) [9]. Occupational exposure to substances such as wood dust, coal dust, welding fumes, asbestos and formaldehyde has been reported to promote the development of HNSCC [10]. HNSCC can also be the result of germline mutations, with Fanconi anemia being the most well-known example Research Paper [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Betel quid chewing, which is popular in India and other Asian countries, has also been shown to increase the risk of HNSCC (mainly oral cancer) [9]. Occupational exposure to substances such as wood dust, coal dust, welding fumes, asbestos and formaldehyde has been reported to promote the development of HNSCC [10]. HNSCC can also be the result of germline mutations, with Fanconi anemia being the most well-known example Research Paper [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mesothelioma and lung cancer, asbestos has also been implicated as a risk factor for cancers involving the upper airway, in particular laryngeal and pharyngeal SCC (4,(12)(13)(14); however, the evidence thus far has been primarily based on epidemiologic data from observational studies. Therefore, the goal of this study was to strengthen the existing evidence implicating asbestos as a risk factor for pharyngeal and/or laryngeal SCC via confirmation of persistent asbestos fibers in epithelial tissue surrounding laryngeal and pharyngeal SCC in cases with a history of occupational asbestos exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Welding fumes are recognized as a group 1 carcinogen in humans because numerous studies have reported an increased risk of lung cancer due to such fumes [3,4]. In addition, chronic welding fume exposure has been reported to exhibit a relationship with lung cancer in welders with no or mild smoking habits [5], as well as pharynx and larynx cancer [6,7,8].…”
Section: Introductionmentioning
confidence: 99%